The Relationship Between Leg Muscle Strength and Shooting Ability in Futsal Among Elementary School Students at IKIP 1 Makassar - Febrianto Sandi Lebang; Putra Putra; Hilman Ashari; Muh Wahyu Anugrah (Journal of Physical Education, Sport, and Human Performance, 2025)
This study aims to determine the relationship between leg muscle strength and shooting ability in futsal among elementary school students at IKIP 1 Makassar. The study used a correlational quantitative method with a total sample of 30 students who actively participated in futsal training. Leg muscle strength was measured using leg press and squat jump tests, while shooting ability was measured based on kicking accuracy and speed. Data were analyzed using descriptive statistics and Pearson's correlation with a significance level of α = 0.05. The results showed that the average leg muscle strength score of the students was 45.3 ± 6.2 kg, while the average shooting ability was 78.5 ± 8.4. Correlation analysis showed a positive and significant relationship between leg muscle strength and shooting ability (r = 0.672, p < 0.05). This indicates that the higher the leg muscle strength, the better the students' shooting ability. These findings emphasize the importance of leg muscle strengthening exercises as part of the PJOK learning program and futsal training to improve kicking technique performance in elementary school students.